The Influence of Service Quality on Customer Loyalty in Hotel Chains: A Moderating Effect of Hotel Star Rating - Sritubtim, Supachai; Darawong , Chonlatis; Wisittigars, Boonkiat (The Journal of Development Administration Research, 2025)
This research aimed to examine the effects of service quality factors on customer loyalty among hotel guests in Thailand, with the Hotel Star Ratings serving as a moderating variable in the relationship. The study applied the Service Quality conceptual framework, which consists of five dimensions: physical environment, courtesy, staff competence, empathy, and reliability. These dimensions were treated as independent variables, while customer loyalty was considered the dependent variable. A quantitative research method was employed, using a questionnaire distributed to 591 hotel customers across Thailand. Data were analyzed using descriptive statistics, exploratory factor analysis, and structural equation modeling (SEM). The results of the study found that the 4 factors of service quality, consisting of physical environment, courtesy, staff competence, empathy, and reliability, had a statistically significant positive influence on customer loyalty (p < 0.05) since customers perceive politeness as something that every hotel should naturally possess, it is not considered a factor that creates differentiation or adds value in their decision to revisit the service. Customer loyalty, therefore, arises more from factors that influence the actual service experience and trust in the service, such as convenience, cleanliness, promptness, and attentiveness to customers’ needs, while the courtesy dimension showed no significant effect. Moreover, the hotel star rating was found to have a moderating effect on the relationship between service quality and customer loyalty at a statistically significant level. The findings of this study can be applied to enhance marketing and service strategies to strengthen customers’ intention to continue using hotel services in Thailand.